Mechanical prophylaxis to prevent venous thromboembolism on stroke patient: a Literature Review - Erna Fitriani; I Made Kariasa (Media Keperawatan Indonesia, 2023)
Prevention of Venous Thromboembolism (VTE) is important in the treatment of stroke, including pharmacological and mechanical thromboprophylaxis. One of the post-stroke complications is Deep vein thrombosis (DVT), DVT can lead to pulmonary embolism (PE), and Venous thromboembolism (VTE) is manifested as DVT and PE. Stroke patients are at increased risk of developing DVT. This review aims to assess the clinical efficacy of mechanical prophylaxis for preventing venous thromboembolism in stroke patients. The articles were searched through PubMed, ScienceDirect, Sage Journals and ProQuest database. Keywords: "Stroke", "Prevention", "Deep Vein Thrombosis", “Venous Thromboembolism”, “Intermittent Pneumatic Compression”, and “Stocking Compression” combined using the Boolean operators AND or OR. The articles were full text, written in English, published in the last 10 years, and provided information about mechanical prophylaxis for preventing VTE in stroke patients. This review provides important information on VTE prevention in stroke patients. The use of IPC significantly reduces the risk of DVT and the addition of IPC in pharmacological prophylaxis provides moderate benefits in VTE, whereas the use of graduated compression stocking is less clinically significant in the prevention of VTE. The use of IPC is an effective method to reduce the risk of VTE in post-stroke immobilized patients, with fewer skin side effects compared to stocking compression.